Influence of Supplementing Pasture-Based Primiparous Holstein-Friesian Dairy Cows with Crude Degummed Canola Oil on Milk Fatty Acid Composition - Malau-Aduli, Aduli Enoch; Otto, John Roger; Malau-Aduli, Bunmi Sherifat; Nichols, Peter David (Journal of Nutritional Therapeutics, 2014)
The quest for alternative sources of healthy nutrients that facilitate the modification of milk without compromising drinking quality is a continuous research endeavour. The objective of the study was to the milk fatty acid composition of pasture-based primiparous Holstein-Friesian dairy cows with crude canola oil (CDCO) with a view to improving the milk quality for beneficial health effects. This study tested the hypothesis that incremental supplementation of grazing primiparous Holstein-Friesian cows with CDCO will alter milk fatty acid composition towards increased total monounsaturates. Comparisons were made between unsupplemented grazing dairy cows and their peers on dietary supplements containing low (25ml/Kg DM), medium (35ml/Kg DM) or high levels (50ml/kg DM) of CDCO in addition to ad libitum grazing access to . There was no significant effect (p>0.05) of CDCO supplementation for eight weeks the proportions of total polyunsaturated fatty acids (tPUFA), omega-3 (ω-3) and omega-6 (ω-6) fatty acids in milk. However, significant impacts of CDCO observed on the proportions of 18:1ω9c, 18:1ω7t, total saturated (tSFA) and total monounsaturated (tMUFA) fatty acids (p<0.005), with a significant increase in the tMUFA/tSFA ratio in cows consuming CDCO. It was concluded that incremental levels of CDCO supplementation can modify the fatty acid composition of milk towards increased monounsaturates without any negative impact on grazing primiparous cows